Single-surgeon outcomes of open radical cystectomy for muscle-invasive bladder cancer: Experience from a tertiary center in Azerbaijan - Rashad Sholan; Rufat Aliyev; Seymur Karimov; Jamal Musayev; Anar Almazkhanli; Rahman Ismayilov (Surgery in Practice and Science)
Summary: Objective: Radical cystectomy is the standard treatment for muscle-invasive bladder cancer (MIBC). This study presents the first analysis of open radical cystectomy (ORC) outcomes in Azerbaijan, where robotic surgery is unavailable. Methods: We retrospectively analyzed 106 patients with non-metastatic MIBC who underwent ORC with bilateral pelvic lymph node dissection and Bricker ileal conduit reconstruction, performed by a single surgeon between 2014 and 2024. Demographic data, comorbidities, operative metrics (duration, blood loss), complications, length of stay, and follow-up data were analyzed. Results: The cohort's mean age was 64.2 years (72.6 % male), with common comorbidities including hypertension (33 %), diabetes (33 %), and coronary artery disease (24.5 %). The median operative time was 300 min and blood loss was 450 mL. Postoperative complications occurred in 9.4 %, primarily urinary tract infections. No intraoperative complications or in-hospital mortalities occurred. Longer hospital stays were associated with advanced age (p < 0.001), higher body mass index (p = 0.042), longer operative time (p < 0.001), and increased blood loss (p = 0.008). Of all patients, 58.5 % were followed for a median of 71.3 months with no observed recurrences. There were three non-cancer related deaths. Conclusion: This initial report from Azerbaijan demonstrates acceptable perioperative outcomes for ORC in MIBC, despite the absence of robotic surgery. Our findings emphasize optimizing surgical efficiency, comorbidity management, and strengthening follow-up to enhance patient outcomes in resource-limited settings.